2020
DOI: 10.3390/cancers12051278
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitising Cancer Using Phosphatidylinositol-3-Kinase (PI3K), Protein Kinase B (AKT) or Mammalian Target of Rapamycin (mTOR) Inhibitors

Abstract: Radiotherapy is routinely used as a neoadjuvant, adjuvant or palliative treatment in various cancers. There is significant variation in clinical response to radiotherapy with or without traditional chemotherapy. Patients with a good response to radiotherapy demonstrate better clinical outcomes universally across different cancers. The PI3K/AKT/mTOR pathway upregulation has been linked to radiotherapy resistance. We reviewed the current literature exploring the role of inhibiting targets along this pathway, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 108 publications
(147 reference statements)
4
51
0
Order By: Relevance
“…Activation of PI3K/AKT has been related to breast cancer and currently, there is a lot of interest in the development of inhibitors of this pathway to target breast cancer 14 . Besides, PI3K/AKT/mTOR pathway upregulation has been linked to chemotherapy and radiotherapy resistance 15 and its inhibition overcome drug resistance in breast cancer cells 16,17 . Another pathway suggested by our analysis was the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PI3K/AKT has been related to breast cancer and currently, there is a lot of interest in the development of inhibitors of this pathway to target breast cancer 14 . Besides, PI3K/AKT/mTOR pathway upregulation has been linked to chemotherapy and radiotherapy resistance 15 and its inhibition overcome drug resistance in breast cancer cells 16,17 . Another pathway suggested by our analysis was the MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…miR-451a is a known and established regulator of the PI3K/AKT pathway via downstream targets like AMPK [ 87 , 88 ]. In this context, the PI pathway has been linked to resistance to radiation, and inhibitors of this pathway are currently being trialled in an attempt to restore radiation sensitivity in different cancer types [ 89 ]. An involvement of miR-451a activated PI3K/AKT pathway in the resistance to radiation therefore seems likely in OAC.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant upregulation and activation of PI3K/AKT/mTOR pathway is also correlated with resistance radiotherapy. A number of preclinical studies indicated that inhibition of PI3K/AKT/mTOR pathway can sensitize different types of cancer cells, including non-small cell lung cancer, breast cancer, nasopharyngeal carcinoma, oral squamous, and head and neck cancer, to radiotherapy ( Yu et al, 2017 ; Chen et al, 2020b ; Chen et al, 2020c ; Glorieux et al, 2020 ; Schötz et al, 2020 ; Wanigasooriya et al, 2020 ). In breast cancer, IL-6 pre-treatment followed by SIRT1 activation by SRT1720 combined with dual PI3K/mTOR inhibitor NVP-BEZ235 obviously increased sensitivity of the cancer stem cells to radiation, so that late stage breast cancer cells therapeutic effect was effectively improved ( Fatehi et al, 2018 ; Masoumi et al, 2020 ).…”
Section: Pi3k/akt/mtor Pathway Induces Drug Resistance In Breast Cancmentioning
confidence: 99%